Common Fixed Point Results for Self-Mappings in Generalized Fuzzy Cone Metric Spaces - Manjeet,; Singh, Ranbir (Communications in Mathematics and Applications, 2025)
A number of generalized contraction results already existed in Cone Metric Space (CMS), Fuzzy Metric Space (FMS) and generalized Fuzzy Cone Metric (FCM) spaces. In the present manuscript, we established some Common Fixed Point (CFP) results in generalized FCM spaces for compatible and weakly compatible self-maps using continuity and without continuity. We establish a new class of Fuzzy Cone Contraction (FCC) theorems extending existing results in the literature including some related examples to these outcomes.
Keywords: Common fixed point; Contraction conditions; Fuzzy cone metric space; Weakly compatible; Self mapping